Immanuel Wallerstein's Theory of the World System, Geopolitics and Geoculture - Zaman Asad (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
A world system theorist, Immanuel Wallerstein attempts to describe a modern world system covering economic, political and cultural areas. In his theory, he argues that the conflicts between the countries which determine the world order in these areas are not true conflicts because the modern world system is built on a capitalist economic basis. He regards powerful states such as the United States of America, Russia, Japan and European States, which seem to be engaged in a competition, as global collaborators of a single modern world system. At the head of this cooperation is the United States of America and the world system is based on the hegemony of the United States of America. Wallerstein maintains that the modern world system is fragile due to economic crises that are likely to arise and regards the period we are in as a post-liberalism period where this hegemony has begun to collapse.